مصطلح الخِصَام في القرآن الكريم دراسة دلاليَّة موضوعيَّة: The Term “Dispute” in Holy Quran: Semantic and Thematic Study - Ismail Abu Helaleh, Mokhled (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
This study is considered important due to Islamic communities need to understand term “dispute” and its types and regulations in the Holy Quran. So this study aims to examine term “ dispute” and its meanings in the context of the Qur’an through the inductive and analytic scientific method to determine concept of the term “dispute” in its context to achieve objects of this study and get answered questions of this study.